Pre-therapeutic UGT1A1 genotyping to reduce the risk of irinotecan-induced severe toxicity: Ready for prime time. (December 2020) - Hulshof, Emma C.; Deenen, Maarten J.; Guchelaar, Henk-Jan; Gelderblom, Hans
Abstract: Background: Pre-therapeutic UGT1A1 genotyping is not yet routinely performed in most hospitals in patients starting irinotecan chemotherapy. The aim of this position paper was to evaluate the available evidence and to assess the potential value of genotyping of UGT1A1 ∗ 2 8 and UGT1A1*6 in patients before starting treatment with irinotecan to reduce the risk of severe toxicity. Methods: The literature was selected and assessed based on five pre-specified criteria: 1) the level of evidence for associations between UGT1A1 polymorphisms and irinotecan-induced severe toxicity, 2) clinical validity and utility of pre-therapeutic genotyping of UGT1A1, 3) safety and tolerability of irinotecan in carriers of UGT1A1 polymorphisms, 4) availability of specific dose recommendations for irinotecan in carriers of UGT1A1 polymorphisms, 5) evidence of cost benefits of pre-therapeutic genotyping of UGT1A1 . Results: On all five criteria, study results were favourable for pre-therapeutic genotyping of UGT1A1 . A high level of evidence (level I) was found for a higher incidence of irinotecan-induced severe toxicity in homozygous carriers of UGT1A1*28 or UGT1A1*6 . The clinical validity and utility of this genetic test proved to be acceptable. Dose-finding studies showed a lower maximum tolerated dose in homozygous variant allele carriers, and most of the drug labels and guidelines recommend a dose reduction of 25–30% in these patients. In addition, pre-therapeutic genotyping of UGT1A1 is likely to save costs. Conclusion: Pre-therapeutic genotyping of UGT1A1 in patients initiating treatment with irinotecan improves patient safety, is likely to be cost-saving, and should, therefore, become standard of care. Highlights: Pre-therapeutic UGT1A1 genotyping improves patient safety. Pre-therapeutic UGT1A1 genotyping is likely cost-saving. UGT1A1 genotyping before starting irinotecan treatment should be standard of care.